2016
DOI: 10.1016/j.tplants.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Diversity of Plant Organelle RNA Editosomes

Abstract: Flowering plants convert many hundreds of organelle cytidines (Cs) to uridines (Us) during post-transcriptional RNA editing. Pentatricopeptide repeat (PPR) proteins dictate specificity by recognizing RNA sequences near C targets. However, the complete mechanism of the editing machinery is not yet understood. Recently, non-PPR editing factors [RNA editing factor interacting proteins (RIPs)/multiple organellar RNA editing factors (MORFs), organelle RNA recognition motif (ORRM) proteins, organelle zinc-finger (OZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(174 citation statements)
references
References 88 publications
1
173
0
Order By: Relevance
“…5), suggesting that ORRM6 may form oligomers. While the stoichiometry of editing factors present in editosomes is not yet known (Sun et al, 2016), our evidence indicates that the RNA editosomes acting on psbF-C77 and accD-C794 contain one or more RIP/MORF proteins, OZ1, ORRM6, and either PPR protein LPA66 or RARE1, respectively.…”
Section: Orrm6 Is a New And Unusual Component Of Particular Arabidopsmentioning
confidence: 79%
See 2 more Smart Citations
“…5), suggesting that ORRM6 may form oligomers. While the stoichiometry of editing factors present in editosomes is not yet known (Sun et al, 2016), our evidence indicates that the RNA editosomes acting on psbF-C77 and accD-C794 contain one or more RIP/MORF proteins, OZ1, ORRM6, and either PPR protein LPA66 or RARE1, respectively.…”
Section: Orrm6 Is a New And Unusual Component Of Particular Arabidopsmentioning
confidence: 79%
“…RNA editing in the coding regions of mRNAs restores conserved codons and is thought to be a correction mechanism for defective genes at the transcript level (Lutz and Maliga, 2001;Schmitz-Linneweber and Barkan, 2007;ChateignerBoutin andSmall, 2010, 2011;Dalby and Bonen, 2013;Takenaka et al, 2013;Börner et al, 2014;Sun et al, 2016). Different plant species vary in their numbers of organelle RNA editing sites (Bock, 1998(Bock, , 2000Tillich et al, 2005;Li-Pook-Than et al, 2007;Robbins et al, 2009;Wang et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Length variants of PPR repeats have been detected however, with repeats that are longer (L) or shorter (S) than the initially-recognized 35-amino-acid (P) motif (11,15). PLS PPR proteins, which contain ordered series of P, L and S motifs, have been almost exclusively associated with RNA editing in both mitochondria and chloroplasts (16,17). In contrast, PPR proteins exclusively composed of P-type repeats were shown to participate in various aspects of organellar RNA expression ranging from gene transcription to mRNA translation (for review see (12,18)).…”
Section: Introductionmentioning
confidence: 99%
“…The site specificity of the cytidines to be edited in a plant organelle is determined by a crucial cis -acting regulatory sequence 1014 and the RNA editosome that will bind to it. The RNA editosome is composed of nuclear-encoded trans -acting factors that recognize the cis -element and perform RNA editing 15 . Recent extensive genetics studies have revealed that these trans -factors enlisted in the RNA editosome include DYW-type pentatricopeptide repeat (PPR) proteins 1 , RNA-Editing Factor Interacting Protein (RIP) family or Multiple Organelle RNA Editing Factor (MORF) family proteins 16, 17 , RNA-recognition motif (RRM)-containing proteins 1820 , protoporphyrinogen IX oxidase 1 (PPO1) 21 and organelle zinc-finger 1 (OZ1) 22 .…”
Section: Introductionmentioning
confidence: 99%